EGFR/PPARδ/HSP90 pathway mediates cancer cell metabolism and chemoresistance. Issue 3 (8th November 2020) - Gou, Qian; Zhang, Wenbo; Xu, Ying; Jin, Jianhua; Liu, Qian; Hou, Yongzhong; Shi, Juanjuan
Abstract: Epidermal growth factor receptor (EGFR) induces peroxisome‐proliferator‐activated receptor‐δ (PPARδ)‐Y108 phosphorylation, while it is unclear the effect of phosphorylation of PPARδ on cancer cell metabolism. Here we found that EGF treatment increased its protein stability by inhibiting its lysosomal dependent degradation, which was reduced by gefitinib (EGFR inhibitor) treatment. PPARδ‐Y108 phosphorylation in response to EGF recruited HSP90 (heat shock protein 90) to PPARδ resulting in increased PPARδ stability. In addition, PPARδ‐Y108 phosphorylation promoted cancer cell metabolism, proliferation, and chemoresistance. Therefore, this study revealed a novel molecular mechanism of EGFR/HSP90/PPARδ pathway‐mediated cancer cell metabolism, proliferation, and chemoresistance, which provides a strategy for cancer treatment. Abstract : Peroxisome‐proliferator‐activated receptor‐δ (PPARδ) plays an important role in regulating cancer progression, while its transcriptional modification on cancer progression is still unclear. epidermial growth factor receptor‐mediated PPARδ‐Y108 phosphorylation recruited HSP90 to PPARδ leading to increased PPARδ protein stability and activity, subsequently, cancer cell metabolism and chemoresistance.